The Effect of Distribution for a Moving Force - Reda, A.; Forbes, Gareth (Australian Acoustical Society, 2011)
Many types of slender or thin walled structures experience forces which traverse across them. For example: vehicles passing over a bridge, overhead crane operations and liquid "slug" movement in spanning pipelines. This moving force can initiate a large dynamic stress within the structure and is often important for assessing structural fatigue. For many of these force/structure scenarios, modelling of the force as a concentrated point force would be an adequate simplifying approximation. In some cases, however, it may not be appropriate to simplify the distributed force into a single point force. For instance, slug lengths in pipelines can be significant in relation to span lengths. There is currently no guidance in the literature regarding the distribution effect of the force on the response of a structure under a moving force. This paper investigates the dynamic response of an elastic, simply supported beam under the influence of a moving distributed force, with varying distribution to span length ratios. In addition, it examines the speed of the traversing force, which is also highly influential on the dynamic response of the beam. This investigation is undertaken using an explicit transient dynamic finite element formulation of a simply supported beam. Guidelines are provided to discriminate between those scenarios when it is appropriate to simplify a distributed moving force as a concentrated force, and those when it must be modelled as the original distributed force.